Parotid duct injury secondary to shark bite injury: Repair with a Crawford stent. (December 2016) - Highstein, Mallory; Tham, Tristan; Singh, Prabhjyot; Costantino, Peter
Abstract: Introduction: Here we present a unique case of repair of a parotid injury caused by a shark attack. The repair technique is of interest due to the novel use of a Crawford stent, typically reserved for lacrimal duct injuries. Case description: Our patient is a 43-year-old man who suffered a shark bite injury to the face and head ten days prior to surgery. The patient presented with multiple lacerations and a sialocele. During the surgery, a sialendoscope and open incision were used to find the duct laceration. The surgeon decided to utilize a Crawford stent as the stiff metal probe would satisfactorily delineate the structure and anatomy of Stenson's duct. Discussion: Often, diagnosis of parotid gland trauma is missed at the time of injury, leading to later complications. In this procedure, we used a Crawford stent as its intrinsic stiffness allows it to tunnel through the duct easily. Conclusion: Clinicians should have a high level of suspicion for parotid duct injury in a patient presenting with injury to the face, particularly with laceration type injuries. Our patient had a unique injury that required a novel Crawford stent repair over traditional silicone catheters.